Avaliação no ciclo de alfabetização: reflexões sobre os processos avaliativos no contexto da prática - AVIZ, Cynthia Santos de (2021)
This study is the result of a research carried out in a kindergarten and elementary school of Bragança-Pará Municipal Network that had as its object of study the evaluation of learning in the context of the Literacy Cycle. The general objective of the research was to understand how the school develops the evaluation in the literacy cycle and the teachers' perceptions regarding the changes in their evaluative practices with the implementation of the cycle system in the school. The specific objectives were to understand how assessment is established in the Literacy Cycle guidance documents in the context of the Municipal Education Network and the school; to analyze teachers' perceptions regarding the practice of evaluation in the Literacy Cycle, emphasizing the changes occurred and the challenges faced. This study is anchored in the qualitative research approach, with the articulation of two data collection instruments: the document analysis and the open questionnaire. The authors who subsidized the study were: Barreto and Mitrulis (1999), (2001), Mainardes (2006), (2007), Fernandes (2007), (2009), Fetzner (2007) and Hoffmann (2011). In this sense we point out as a certain clarity of the objectives and purposes of the evaluation in the new proposal of organization of elementary school and cycles in the documents of the Municipal School and School, but the teachers still find difficulties in the evaluation process in relation to the instruments and centrality in some areas of knowledge